Alpha and beta diversity of connected benthic–subsurface invertebrate communities respond to drying in dynamic river ecosystems. Issue 12 (17th September 2019) - Stubbington, Rachel; Sarremejane, Romain; Datry, Thibault
Abstract : Drying disturbances are the primary determinant of aquatic community biodiversity in dynamic river ecosystems. Research exploring how communities respond to disturbance has focused on benthic invertebrates in surface sediments, inadequately representing a connected community that extends into the subsurface. We compared subsurface and benthic invertebrate responses to drying, to identify common and context‐dependent spatial patterns. We characterized community composition, alpha diversity and beta diversity across a gradient of drying duration. Subsurface communities responded to drying, but these responses were typically less pronounced than those of benthic communities. Despite compositional changes and in contrast to reductions in benthic alpha diversity, the alpha diversity of subsurface communities remained stable except at long drying durations. Some primarily benthic taxa were among those whose subsurface frequency and abundance responded positively to drying. Collectively, changing composition, stable richness and taxon‐specific increases in occurrence provide evidence that subsurface sediments can support persistence of invertebrate communities during drying disturbances. Beta‐diversity patterns varied and no consistent patterns distinguished the total diversity, turnover or nestedness of subsurface compared to benthic communities. In response to increasing drying duration, beta diversity increased or remained stable for benthic communities, but remained stable or decreased for subsurface communities, likely reflecting contrasts in the influence of mass effects, priority effects and environmental filtering. Dissimilarity between subsurface and benthic communities remained stable or increased with drying duration, suggesting that subsurface communities maintain distinct biodiversity value while also supporting temporary influxes of benthic taxa during drying events. As temporary rivers increase in extent due to global change, we highlight that recognizing the connected communities that extend into the subsurface sediments can enable holistic understanding of ecological responses to drying, the key determinant of biodiversity in these dynamic ecosystems.